Niewydolność serca i płuc, transplantologiaImplementation of lung transplant programme in Poland creates a chance for treatment of patients with irreversible lung disease - Wojarski, Jacek; Żegleń, Sławomir; Przybylski, Roman; Jastrzębski, Dariusz; Sioła, Mirosława; Drżał, Karina; Nożyński, Jerzy; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
The first heart transplant programme in Poland was initiated in 1985 in the Silesian Centre for Heart Diseases by Professor Zbigniew Religa. It has been developed successfully since then, and today it involves more than 800 OHT patients. The idea of the Heart and Lung Transplant Programme arose in Zabrze on the initiative of Professor Marian Zembala and his co-workers. In 2001 the Heart and Lung Transplant Programme was started, and in 2002 the Single Lung Programme. It has taken a few years, however, to begin the first programme of lung transplantation in Poland. Developed in the Silesian Centre for Heart Diseases in 2004, with successful co-operation of the best professional team of transplantologists, anaesthesiologists, pulmonologists and cardiologists, so far this programme has involved 21 transplants: of single lung, double lung, heart and lung. The great experience of the Centre, supported by frequent training, courses and co-operation with well-known, recognised transplant centres abroad, such as one in Hannover (Professor A. Haverich, Dr. A. Simon) and one in Pittsburgh (Dr. Y. Toyoda) may be evidenced by OUT good postoperative short and long-term outcomes: 15 patients after successful lung transplantation were discharged from the hospital with good pulmonary efficiency. The Lung Transplant Programme in Zabrze has been coordinated by Dr. Jacek Wojarski, in co-operation with transplantologists, anaesthesiologists, pulmonologists and cardiologists.